2013
DOI: 10.1002/ange.201302989
|View full text |Cite
|
Sign up to set email alerts
|

Heme Binding Induces Dimerization and Nitration of Truncated β‐Amyloid Peptide Aβ16 Under Oxidative Stress

Abstract: Several observations suggest a link between (ferric) heme and Alzheimers disease (AD), for example, an increase in heme oxygenase 1, [1,2] a loss of complex IV, [3][4][5][6] and abnormal iron metabolism. These observations suggest that heme metabolism is altered in age-related disorders. As a possible explanation, hemin has been proposed to interact with b-amyloid peptides (Ab), [7] and it is now well established that Ab peptides bind ferric heme. [8] The adducts of hemin-Ab peptides also exhibit increased per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
4
10
0
Order By: Relevance
“…It has been reported that Aβ can interact with haem to form five or six-coordinated complex which shows peroxidase activity and can lead to the formation of peptide oligomers containing dityrosine cross-linking in the presence of H 2 O 2 2122. The observed cross-linking process in this work resembles the Aβ cross-linking reported previously21.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It has been reported that Aβ can interact with haem to form five or six-coordinated complex which shows peroxidase activity and can lead to the formation of peptide oligomers containing dityrosine cross-linking in the presence of H 2 O 2 2122. The observed cross-linking process in this work resembles the Aβ cross-linking reported previously21.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we have confirmed that the mechanism of fibrinogen cross-linking via dityrosine formation triggered by haem molecule under non-thermal plasma exposure is similar to the case of Aβ peptides induced by haem molecule under H 2 O 2 stress21. Coordinated fibrinogen-hematin complex shows peroxidase activity and in the presence of plasma-generated H 2 O 2 the complex leads to the cross-linking of the peptides via dityrosine formation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…34 The transfer of an electron from Tyr10 to O 2 will subsequently lead to the formation of a tyrosyl radical that can cause dimerization of the peptides cross-linked via the tyrosine residue, which are characteristic features of AD. 35 The formation of an Fe−O 2 intermediate ( Figure 3C, blue) is the first step involved in the PROS generation pathway by the Fe(II) center, and this intermediate has been trapped and characterized in numerous heme proteins and their synthetic analogues. 36 The Fe−O 2 intermediate involved in the O 2 reduction pathway by heme−Aβ was trapped using picket Figure 4A).…”
Section: •−mentioning
confidence: 99%